Sumbangan Budaya Islam dalam Pelestarian Seni Pertunjukan dan Seni Rupa Tradisional di Jawa - Timbul Haryono (Jurnal Kajian Seni, 2019)
Genuine culture or prehistoric culture, such as: Nusantara, is a culture that was not influenced by foreign culture. However, the development stimulates possibility of culture mixing. The mixing process between that is a dialogical process, which placed the local culture as non-passive culture. The arrival (or expansion, ed) of Islamic culture in Java does not ruin the culture that existed (pre Islamic era), but there was a mixing or acculturation. This paper deals with various wayang as the material of the mixing dialogue. The conclusion of this case is the diffusion or spreading Islamic Art adopted pre-Islam element with cultural acculturation, then the continuity of Javanese culture keep continues. In other hand, the existence of traditional art is maintained.